Robotic compared with conventional laparoscopic hysterectomy: a randomized controlled trial - Sarlos, Dimitri; Kots, LaVonne; Stevanovic, Nebojsa; von Felten, Stefanie; Schär, Gabriel (Obstetrics and gynecology (New York. 1953), 2012)
To compare surgical outcome and quality of life of robot-assisted laparoscopic hysterectomy with conventional laparoscopic hysterectomy. For this controlled clinical trial, patients with benign indications for hysterectomy were randomized to receive either a robotic (robotic group) or conventional laparoscopic hysterectomy (conventional group). The primary end point was total operating time; secondary end points were perioperative outcome, blood loss, and the change in quality of life. Ninety-five patients out of 100 randomized patients completed the study. Patient age, body mass index, and uterus weight showed no significant differences between both groups. All results are given as mean (± standard deviation; median). Total operating time for the robotic group was significantly higher with 106 (± 29; 103) compared with 75 (± 21; 74) (conventional group) minutes. Blood loss, complications, analgesics use, and return to activity for both groups were comparable. The change in preoperative to postoperative quality-of-life index (quality of life measured on a linear scale from 0 to 100) was significantly higher in the robotic group, with 13 (± 10; 13) compared with 5 (± 14; 5) (conventional group). Robot-assisted laparoscopic hysterectomy and conventional laparoscopy compare well in most surgical aspects, but the robotic procedure is associated with longer operating times. Postoperative quality-of-life index was better; however, long-term, there was no difference. However, subjective postoperative parameters such as analgesic use and return to activity showed no significant difference between both groups.